Coherent magnetic structures in self-organized plasmas. (4th March 2019) - Pegoraro, F; Bonfiglio, D; Cappello, S; Giannatale, G Di; Falessi, M V; Grasso, D; Veranda, M
Abstract: The concept of Lagrangian coherent structures (LCS) has been recently applied to complex magnetic configurations in plasmas in order to find and characterize their main structural features. LCS make it possible to separate regions inside these configurations where field lines exhibit a different kind of behavior. In the present article, first we review the main features and uses of this technique and then apply it to the study of configurations that evolve into a self-organized quasi-single helicity state referring in particular to results obtained in the reversed-field pinch experiment in Padua.